Seed Germination and Seedling Survivability of Sequoia sempervirens Lamb.) Endl., and Sequoiadendron giganteum (Lindl.) Buch., in Bangalore, South India - Bhaskar, V. (Indian Forester, 1995)
Seed germination and seedling survivability of California giant sequoia (Sequoiadendron giganteum) and redwood (Sequoia sempervirens) were studied for the first time in India. Seed viability appears to differ depending on the source of seed lot and the altitude at which seeds are collected. 24 year-old seeds of S. giganteum from seed lot.J (Fresno Co.) showed 66% germination while 15 year-old seeds from seed lot-N (Tulare Co.) showed only 3% germination. Seeds of S. sempervirens which were 5 year-( mix of lots, Mendocino Co.) and 11-year old (Lot-AK, DelNorte Co.) showed zero and 4% germination respectively. The seedling survivability was also found to be better (55-69%) in case of S. giganteum than S. sempervirens as the former seems to have long viability as well as hardiness.